Clinical characteristics and long-term outcome of patients with gastrointestinal involvement in eosinophilic granulomatosis with polyangiitis - Li, Rongli; Chen, Yingying; Zhang, Shangzhu; Peng, Linyi; Zhou, Jiaxin; Fei, Yunyun; Zhang, Wen; Zhao, Yan; Zeng, Xiaofeng (Frontiers in Immunology, 2023)
Objective: This study aims to investigate clinical characteristics, potential risk factors, as well as long-term outcome in EGPA patients with GI involvement. Methods: A total of 94 EGPA patients were included in this cohort study. We retrospectively reviewed the clinical data, treatment, and outcome of 21 EGPA patients with GI involvement and compared them with other 73 EGPA patients without GI involvement. Multivariate logistic regression was used to find potential risk factors associated with GI involvement in EGPA patients. Results: Compared with EGPA patients without GI involvement, EGPA patients with GI involvement had higher level of hs-CRP (65.1 (24.5-138.9) vs. 21.3 (5.7-39.1) mg/L, p=0.005), higher grades of Birmingham vasculitis activity score (BVAS) (20 (13-29.5) vs. 12 (16-19), p=0.022), higher Five Factor Score (FFS) (1 (1-2) vs. 0 (0-1), p<0.001), and were more likely to have weight loss (66.7% vs. 38.4%, p=0.021) at baseline. In EGPA patients with GI involvement, the most common gastrointestinal symptoms were abdominal pain (90.5%) and diarrhea (42.9%). Weight loss was identified as a potential risk factor for GI involvement in EGPA patients (OR = 4.304, 95% CI 1.339–13.841). During follow-up, EGPA patients with GI involvement showed lower 1-year cumulative survival rate (75.2% vs. 100.0%, P <0.0001) and 3-year cumulative survival rate (67.7% vs. 100.0%, P<0.0001), lower long-term remission rate (33.3% vs. 86.3%, P<0.001), but higher 1-year cumulative relapse rate (19.2% vs. 3.8%, P=0.03) and 3-year cumulative relapse rate (54.6% vs. 13.1%, P<0.001) compared with patients without GI involvement. Conclusion: EGPA patients with GI involvement had distinct features from those without GI involvement, including higher hs-CRP level, higher BVAS and FFS scores. EGPA patients with GI involvement showed lower cumulative survival rate, lower long-term remission rate and higher cumulative relapse rate compared with those without GI involvement.